Work autonomy, communication openness, and self-efficacy in driving individual innovation - Hidayat, Ferry; Sherly, Sherly; Victor, Victor (Institute of Computer Science (IOCS), 2026)
This study aims to analyze the effects of work autonomy, communication openness, and self-efficacy on individual innovation among employees of PT. Karya Bersama. Individual innovation plays a crucial role in enhancing organizational performance, as it contributes to the development of new ideas, improvement of work processes, and overall work quality. Therefore, understanding the factors that influence individual innovation is essential for organizations seeking to remain competitive. This research adopts a quantitative approach using a survey method, with data collected through structured questionnaires distributed to employees of PT. Karya Bersama. A total of 47 respondents were selected using a saturated sampling technique. The collected data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that work autonomy has a positive and significant effect on individual innovation. Similarly, communication openness also shows a positive and significant influence on individual innovation. In contrast, self-efficacy does not have a significant effect on individual innovation. Furthermore, the simultaneous analysis reveals that all independent variables collectively influence individual innovation, with an adjusted R² value of 0.586, indicating that 58.6% of the variation in individual innovation is explained by the model. These findings suggest that enhancing individual innovation can be achieved by strengthening work autonomy and promoting open communication within the organization.